Shifting linguistic identity performance and the acquisition of symbolic capital in an online white nationalist forum - Booth, Amy (Language and Law / Linguagem e Direito, 2025)
This article contributes to a small existing literature which seeks to identify linguistic power resources in harmful online communities, using a dataset taken from a long-running, high profile white nationalist forum to longitudinally explore users’ development of power resources over time. By improving understanding of the nature of power in such communities, this work can aid law enforcement in the investigative prioritisation of high-status community members. To do so, I combine Newsome-Chandler & Grant’s (2023) linguistic resource model of power with Bourdieu’s (2004) concept of symbolic capital, tying the former into a broader, more generalisable understanding of available power resources, while anchoring the latter in a more concrete model of how power may operate discursively in local contexts. My findings show that, surprisingly, users draw on fewer traditional power resources over time, producing less explicitly assertive and extreme discourse. They also begin to treat the forum as a social, rather than solely ideological, space, and increasingly focus criticism on their white (nationalist) in-group, rather than racialised out-groups. I also show that users rely on non-linguistic forms of symbolic capital as secondary, non-linguistic power resources.